(untitled) (LACCEI, 2024)
Healthy eating behaviours are of particular interest to nutrition education. In Ecuador, children in rural areas are the main concern because they carry a higher burden of malnutrition compared to urban areas. In this study, we grouped rural children according to their attitudes, social influences, and self-efficacy in terms of latent variables, using school type as a concomitant variable to predict latent class membership. The study included rural children studying in 3 different schools involving thereby a) all students from 2nd till 5th grade in a single classroom setting who are taught by only one teacher (n=12), b) students of one 3rd grade in a conventional school (n=29), c) students of two 3rd grade courses in a Millennium School (n=38). We estimate that children learning in traditional schools with less modern infrastructure (school A and B) have a high probability of having low self-efficacy to traditional foods (TFs) and are more oriented to follow parental norms when eating TFs. The low self-efficacy to TFs of these children could possibly be explained by the low quality of education received in these schools. These conclusions could be used to implement future interventions to promote the consumption of TFs and fight malnutrition among children living of Guasaganda.